Pengembangan Modul Elektronik Interaktif untuk Meningkatkan Minat dan Kemandirian Belajar Informatika di SMK Negeri 1 Pajangan - Akhi Ha Runi Nur Rahayu; Deni Hardianto; Bait Syaiful Rijal (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aimed to develop and analyze the effectiveness of an interactive electronic module in enhancing students’ interest and independent learning in the Informatics subject. The research method used was Research and Development (R&D) with the ADDIE model, which included analysis, design, development, implementation, and evaluation. The analysis phase involved observations, questionnaire distribution, curriculum review, and interviews. The module design included identifying subject elements, setting minimum competency criteria, and designing assessment forms. The module development process involved creating learning content, supporting media, and making formative revisions based on initial trials and expert validation. The module was tested by subject matter and media experts, as well as through field trials involving 34 students from SMK Negeri 1 Pajangan using a pre-experimental design. The research results indicated that the module was highly feasible for use, receiving a score of 3.93 from subject matter experts and 3.92 from media experts. The module's practicality was also rated highly by students, with a score of 3.71. In terms of effectiveness, there was an increase in students' learning interest with a gain score of 0.48 and independent learning with a gain score of 0.57 (moderate category), with 82% of students meeting the minimum competency criteria. These findings suggested that the developed module was effective in supporting Informatics learning.